2020
DOI: 10.3389/fimmu.2020.02009
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol Has the Capacity to Increase Transcription Factor Expression and Cytokine Production in Porcine T Cells

Abstract: Deoxynivalenol (DON) is a Fusarium mycotoxin that frequently contaminates the feed of farm animals. Pigs with their monogastric digestive system are in particular sensitive to DON-contaminated feed. At high concentrations, DON causes acute toxic effects, whereas lower concentrations lead to more subtle changes in the metabolism. This applies in particular to the immune system, for which immunosuppressive but also immunostimulatory phenomena have been described. Research in human and rodent cell lines indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…In vitro work from the authors of this study could show that mitogen-induced proliferation and the expression of the co-stimulatory molecules CD27 and CD28 of porcine T cells is negatively affected by doses ≥ 0.8 μM of DON (Vatzia et al 2019 ). However, a follow-up study revealed that a dose of 0.8 μM of DON is capable to increase T-bet expression and production of IFN-γ and TNF-α in porcine CD4 + and CD8 + T cells (Vatzia et al 2020 ), reminiscent of in vivo observations in this study. However, such effects seem to occur in a small dose-dependent window; in vitro work by Hlavová et al ( 2020 ) showed that porcine CD4 + and γδ T cells have a reduced production of IFN-γ, TNF-α and IL-17 following polyclonal stimulation in the presence of 0.034 µM DON.…”
Section: Discussionsupporting
confidence: 60%
“…In vitro work from the authors of this study could show that mitogen-induced proliferation and the expression of the co-stimulatory molecules CD27 and CD28 of porcine T cells is negatively affected by doses ≥ 0.8 μM of DON (Vatzia et al 2019 ). However, a follow-up study revealed that a dose of 0.8 μM of DON is capable to increase T-bet expression and production of IFN-γ and TNF-α in porcine CD4 + and CD8 + T cells (Vatzia et al 2020 ), reminiscent of in vivo observations in this study. However, such effects seem to occur in a small dose-dependent window; in vitro work by Hlavová et al ( 2020 ) showed that porcine CD4 + and γδ T cells have a reduced production of IFN-γ, TNF-α and IL-17 following polyclonal stimulation in the presence of 0.034 µM DON.…”
Section: Discussionsupporting
confidence: 60%
“…Total leukocyte and neutrophil percentages indicate a more grossly sustained pro-inflammatory response, with CD4 − CD8 + lymphocytes and the CD4:CD8 ratio responding more sensitively. Decreased proliferation of CD4 − CD8 + , CD4 + CD8- and CD4 + CD8 + porcine T cells with DON exposure at levels greater than 0.4 µM and reduced proliferation of peripheral blood mononuclear cells (PBMCs, primarily lymphocytes of unknown CD4/8 phenotypes) in cattle at DON levels as low as 0.21 µM have been observed [ 13 , 25 ]. While true absorption of DON in steers of this study is unknown, even a conservative estimate of blood volume (425 kg average body weight, 9 kg TMR intake/day [ 24 ]) would conclude that cytotoxic DON levels are reported to perturb PBMCs from this species [ 13 ] would be attainable only with a high absorption and distribution of the parent toxin.…”
Section: Resultsmentioning
confidence: 99%
“…As a next step, the gut co-culture model stimulated by ConA was used to study the role of potential immunomodulators on ongoing inflammatory reactions in the intestine. ConA is known as a potent antigen-independent mitogen that functions as an inducer, leading T cells to polyclonal proliferation and cytokine in- duction [30,34]. Various nutritional strategies are implemented to help piglets to cope with the post-weaning period and overcome weaning-related difficulties [35][36][37].…”
Section: Discussionmentioning
confidence: 99%